The Influence Of Financial Transparency On Community Participation In The Management Of Village Funds: A Study Of Srigunting Village - Nabila Nahda Maliha Samudra; Agus Tripriyono; Hendra Saputra; Ayu Kurnia Sari (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study examines how financial transparency influences community participation in the management of village funds in Srigunting Village. The background of this research arises from the relatively low level of community involvement in deliberation, planning, and supervision of village funds, which is presumed to be related to the delivery of financial information that is not yet fully accessible and easily understood. This study focuses on three main aspects: the level of financial transparency, the level of community participation, and the relationship between the two. Theoretically, this research is supported by the concepts of financial transparency and community participation, as well as Agency Theory and Stewardship Theory, which emphasize the importance of information disclosure in building public trust. The results indicate that the village government has provided information through public deliberations and budget reports; however, there are still limitations in how the information is presented, making it difficult for some community members to fully comprehend the reports. This condition affects the level of community involvement, suggesting that the clearer and more transparent the information.